IT OUTSOURCING SUCCESS FACTORS FOR THE CLIENT ORGANIZATION - Jimmy Jimmy (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2008)
Information and Technology Outsourcing (ITO), as defined by Willcocks et al.[1], is the practice of sourcing all or part of an organization‘s IT and IS functions along with its related services from an outside vendor. Due to the huge sum of money involved on each ITO contract, ITO managers were under pressure to successfully deliver what has been expected from the contract. This paper will focus on synthesizing ITO success factors from the current literatures to suggest a complete list of factors which influence the ITO success for the client organization. Based from the literatures, the following list of factors is proposed as the ITO key success factors: selective outsourcing, client core capabilities, relationship, ITO process, ITO configuration fit, supplier capabilities, ITO contract and stakeholder management. With a clear understanding on both the expectations and the success measurements, an ITO manager could use the proposed key success factors to enhance the success of his/her outsourcing ITO contract. Keywords: Information Technology Outsourcing, Key Success Factor